Relationship between P Wave Dispersion and Left Ventricular Diastolic Dysfunction in Hypertensive and Ischemic Heart Disease Patients (Cardiovascular Journal, 2015)
Background: There is growing recognition that congestive heart failure caused by a predominant abnormality in left ventricular diastolic function is common and causes significant morbidity and mortality. Diastolic function usually declines before systolic function, and this precedes clinical signs. 12-lead electrocardiogram is a commonly used tool to assess left atrial enlargement, which is a marker of left ventricular diastolic dysfunction. We investigated the relationship between P wave dispersion, which is easily measured on the surface electrocardiogram and left ventricular diastolic function.Methods: There were 100 patients: 50 with diastolic dysfunction and 50 without. P wave dispersions were calculated by measuring minimum and maximum P wave duration values on the surface electrocardiogram. The relationships between P wave dispersion and echocardiographic measurements of diastolic dysfunction were assessed.Results: Maximum P wave duration was observed significantly (p=0.001) in patients with left ventricular diastolic dysfunction (119.60±8.2 ms vs 114.0±6.4 ms). Minimum P wave duration was observed significantly (p=0.001) higher in patients without diastolic dysfunction (72.6±7.5 ms vs 62.70±7.4 ms). P wave dispersion was observed significantly (p=0.001) higher in patients with left ventricular diastolic dysfunction (56.6±6.3 ms vs 41.5±5.2 ms). When patients were grouped according to grades of diastolic dysfunction, P wave dispersion was observed sequentially increased among 3 grades of left ventricular diastolic dysfunction (55.8±5.2 ms vs 55.9±7.0 ms vs 61.4±4.7) but the differences were not statistically significant (p=0.09).Conclusion: We conclude that P wave dispersion increases in diastolic dysfunction of LV. When clinical and echocardiographic variables are taken into account, there is a weak but significant correlation between P wave dispersion and left ventricular ejection fraction.Cardiovasc. j. 2015; 8(1): 13-18